Home enteral nutrition - Camilo, M. Ermelinda (1997)
The quality of home enteral nutrition must rely on a network between hospital nutritional teams and primary care. Major issues are the selection of patients and acess route. Percutaneous endoscopic gastrostomy, properly managed, maybe the best option for the medium-long term cases.